Minimal reducts with Grasp - Mendez-Gurrola, Iris Iddaly (2011)
The proper detection of patient level of dementia is important to offer the suitable treatment. The diagnosis is based on certain criteria, reflected in the clinical examinations. From these examinations emerge the limitations and the degree in which each patient is in. In order to reduce the total of limitations to be evaluated, we used the rough set theory, this theory has been applied in areas of the artificial intelligence such as decision analysis, expert systems, knowledge discovery, classification with multiple attributes. In our case this theory is applied to find the minimal limitations set or reduct that generate the same classification that considering all the limitations, to fulfill this purpose we development an algorithm GRASP (Greedy Randomized Adaptive Search Procedure).